2020
DOI: 10.48550/arxiv.2012.13455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling Disease Progression in Mild Cognitive Impairment and Alzheimer's Disease with Digital Twins

Daniele Bertolini,
Anton D. Loukianov,
Aaron M. Smith
et al.

Abstract: Alzheimer's Disease (AD) is a neurodegenerative disease that affects subjects in a broad range of severity and is assessed in clinical trials with multiple cognitive and functional instruments. As clinical trials in AD increasingly focus on earlier stages of the disease, especially Mild Cognitive Impairment (MCI), the ability to model subject outcomes across the disease spectrum is extremely important. We use unsupervised machine learning models called Conditional Restricted Boltzmann Machines (CRBMs) to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…We evaluate these aging trajectories by comparing with the observed test population. We train a logistic regression classifier to evaluate if the synthetic and observed populations can be distinguished [18,19,42,43]. We find that this classifier has below a 57% accuracy for the first 14 years past baseline (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluate these aging trajectories by comparing with the observed test population. We train a logistic regression classifier to evaluate if the synthetic and observed populations can be distinguished [18,19,42,43]. We find that this classifier has below a 57% accuracy for the first 14 years past baseline (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, other machine learning models of aging or aging-related disease progression have been emerging [12,[18][19][20]43]. Since they each differ significantly in terms of both the datasets, types of data used, and scientific goals, it is still too early to see which approaches are best -and for which data and what goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico trials are an ongoing research area aimed at using simulations or machine models to replicate some, if not all, parts of a regular clinical trial. [12] Conditional Restricted Boltzmann Machines Bertolini et al [13] Conditional Restricted Boltzmann Machines Choi et al [14] Generative Adversarial Networks Guan et al [15] Generative Adversarial Networks Cui et al [16] Generative Adversarial Networks Baowaly et al [17] Wasserstein Generative Adversarial Networks Zhang et al [18] Wasserstein Generative Adversarial Networks Biswal et al [19] Variational Auto-encoders Lee et al [20] Auto-encoders and Generative Adversarial Networks Xu et al [21] Conditional Generative Adversarial Networks Biosimulation Eddy and Schlessinger [22] Differential Equations Kovatchev et al [23] Differential Equations Man et al [24] Differential Equations Gillette et al [25] Differential Equations Compte et al [26] Differential Equations Baillargeon et al [27] Differential Equations Zhang et al [28] 3D Printing Low et al [29] 3D Printing Herland et al [30] 3D Printing Yu et al [31] Reinforcement Learning Individualized Predictive Modeling…”
Section: Clinical Simulationmentioning
confidence: 99%
“…They showed that digital subjects generated by the CRBM were statistically indistinguishable from actual subjects enrolled in the placebo arms of clinical trials for MS. Similarly, Bertolini et al [12] described a generative model composed of two CRBMs that accurately simulated subjects with Mild Cognitive Impairment (MCI) and Alzheimer's Disease (AD). They showed that linear classifiers were unable to distinguish actual subjects from their digital twins based on the generated features; Bertolini et al…”
Section: Trial Outcome Predictionmentioning
confidence: 99%